Antioxidant and anti-inflammatory activities of different extracts from aerial parts of Zilla spinosa (L.) Prantl - Mecheri, R.; Mahfouf, N.; Smati, D.; Boutefnouchet, A. (Current Botany, 2023)
Zilla spinosa L. is a medicinal plant widely used in traditional Algerian phytotherapy against urinary lithiasis. The present study aims to evaluate the antioxidant and anti-inflammatory effects of different extracts from the aerial part of this plant. The antioxidant activity of the extracts was examined by two different methods, 2,2-diphenyl-1-picrylhydrazyl (DPPH) and cupric reducing antioxidant capacity (CUPRAC). The anti-inflammatory activity of Z. spinosa was determined by the protein denaturation method. The qualitative phytochemical screening shows the presence of the majority of secondary metabolites in the aerial parts except anthraquinones and steroids, on the other hand, the root is characterized by the absence of several metabolites except tannins and coumarins.The ethyl acetate fraction displayed the highest antioxidant capacity (IC50 value: 10.47±0.18 μg/mL in DPPH assay, and A0.50 value: 40.89 ± 0.86 μg/mL in CUPRAC). The percentage of inhibition of BSA denaturation (0.2%) is proportional to the concentration of the different plant extracts, where the highest percentage was recorded in the concentrations of ethyl acetate 500; 250 μg/mL compared to Diclofenac (75 mg/3 mL), in contrast to the aqueous extract which gave non-significant results compared to the standards (p≥5℅). In comparison to the standards used in this study, the ethyl acetate extract demonstrated better DPPH inhibitory activity, while all organic extracts demonstrated lower CUPRAC inhibitory activity but higher anti-inflammatory activity.